Investigation of Purified Sulfate Turpentine on Engine Performance and Exhaust Emission - Yumrutaş, R.; Alma, M.H.; Özcan, H.; Kaşka, O. (Elsevier Sci Ltd, 2008)
This study deals with an experimental work that aims to examine effects of purified sulfate turpentine obtained from a kraft pulp mill in Turkey on an engine performance and exhaust emissions of a spark ignition engine. Three fuel samples are used to test the performance and emission of a 1300 cc engine manufactured by TOFAŞ. They are pure gasoline with 98-octane number and two other gasoline-turpentine fuel samples obtained by blending gasoline with turpentine in ratios of 5% and 10% on basis of total mass of the fuel. The thermophysical properties of the fuels are acquired by density, viscosity, flash and fire points, sulphur content, heating value and distillation tests. The experimental results showed that the turpentine has a positive effect on the engine performance parameters, such as brake power, thermal efficiency, mean effective pressure and specific fuel consumption. The turpentine also increases pollutant NOx, unburned hydrocarbon contents and exhaust temperature, but it decreases CO concentration in the exhaust. It is observed that utilization of the sulfate turpentine alone is not viable and it needs to be used as an additive into gasoline to some extent, thereby providing a viable alternative to pure gasoline. © 2007 Elsevier Ltd. All rights reserved.
Keywords: Alternate Fuel; Biofuel; Emission Analysis; Engine Performance; Turpentine